Students’ error analysis in transforming active voice into passive voice through linguistics category - opan siroj; Ikariya Sugesti (Concept : Community Concern for English Pedagogy and Teaching, 2020)
This study was carried out to analyze and to classify the types of student’s error in transforming active voice into passive voice. The method that was used was descriptive qualitative. The research was designed in a case study. Furthermore, the subject of this study was the second semester students at one of the private university in Cirebon, because four of the students were absent, the researcher took 14 students as the sample. The datas were collected through observation, test for the students and interview to the English lecture. The result of the error analysis showed that students committed error into two types, those were in linguistics category and surface taxonomy. From the frequency of each errror types, past participle incorrect in linguistics category was the error which most frequently produced by the student which consisted of 16 or 73%. Morever, in syntactical errors from the highest and the lowest are disagreement of subject and tenses which consisted of 47 or 60%. In surface taxonomy, the highest error that students made was in misformation which consisted of 61 or 39%, it is followed by error was in omission which consisted of 51 or 33%. It can be concluded that the most students at the second semester students at one of the private university in Cirebon have not mastered yet in transforming active voice into passive voice sentence, especially when the active sentence has two objects. Keywords : Error analysis; Linguistics Category; Surface Taxonomy; Passive Voice